Pengaruh Tata Guna Lahan Terhadap Hidrograf Aliran Di Sub-Sub DAS Keyang-Slahung-Tempuran Menggunakan Model SWAT - M. Khuzaimy Rurroziq Basthoni; Mahendra Andiek Maulana; A.A.Ngr. Satria Damarnegara (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2023)
Generally, area development leads land use changing that may cause surface runoff increases. These alterations are responsible for flood and inundation in certain areas. Soil and Water Assessment Tool (SWAT) can be used to perform rainfall-runoff model. Hence, the flow change can be estimated comprehensively. To ensure the reliability of the model, calibration and validation are required. The calibration and validation stages were conducted using SUFI-2 (Sequential Uncertainty Fitting Version 2) method to determine the most influential or sensitive parameter. Meanwhile, the reliability test was assessed using the , NSE, and PBIAS methods. The reliability test for the calibration and validation provides a good result. In advance, this research shows that the increase of forest area may decreases the peak flow during flood occurrence.